MARKETING APPROACH TO THE FORMATION OF MANAGEMENT SYSTEM FOR ENTERPRISE STRATEGIC DEVELOPMENT IN THE CONTEXT OF GLOBALISATION - Anna V. Shevchenko; Olena S. Borysenko (Journal of International Legal Communication, 2021)
In the context of global consumer and financial market formation, international economic institutions, taking into account special aspects of the present stage in economic development in Ukraine, it becomes necessary to focus enterprises on their own goods competitiveness not only in the domestic, but, moreover, at the foreign markets. In order to achieve objectives in view the enterprise should make maximum use of its internal resources, explore the market environment, predict its development and demands, using all tools of the strategic marketing. Special attention should be paid to the development of marketing strategies since they determine the enterprise course of action and they are aimed at achieving stated targets. Marketing strategy formation is one the most important and essential marketing stages at the enterprise. Marketing strategy is one of the main long-term plans of the enterprise marketing activity, aimed at choosing target consumer segments. It combines elements of marketing complex, basing on which the enterprise creates its effective marketing events targeted to the marketing goals achieving. Successfully chosen and effectively implemented strategy provides enterprise the opportunity to gain competitive advantage not only in the domestic market, but additionally meet demands of international consumers. Based on research of the issue the article highlights the main features of the management system in the strategic development of marketing strategy at the enterprise. The article substantiates the necessity of using marketing approach to the management of enterprises and the finding the new ways in the formation of appropriate organisational structures. Marketing approach to the management of enterprise characterises it as a complex system that allows to link the capabilities of this economic entity with the needs of the market and gain advantages over competitors. It was defined the main factors influencing the organisation of marketing activities of enterprises (external and internal) and factors influencing the behaviour of their end users (social, informational and consumer attitudes).